Engineering multi-agent systems : 6th International Workshop, EMAS 2018, Stockholm, Sweden, July 14-15, 2018, revised selected papers /: 6th International Workshop, EMAS 2018, Stockholm, Sweden, July 14-15, 2018, revised selected papers. (2019) - Unknown
No abstract available